(3GdHGgs - (3YeQh Hf HMQ Hf eMHhH GdcfGfj HGdhdGA, GddjKj, CHh YKeGf, GdLGMX,J (B255 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg GdPj Ndb GdCTjGA HbOQJg SCdJfj Cf CPcQ eG jJMUd ddeJeJYjf aj GdCMGjjf ef EfbWGY GdHGg GdMGQb hGdaJhQ hGdfTGW YfO cKQI GdSQhQ s
(3BNQgG (B:s
(3BNQg eHJhQ, jfJgj CKfGA GdMOjK Yf ChVGY GdLeGY hCTcGdg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B144 - (3U(B156s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B74 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B7s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B35 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs